Elbow Reconstruction Using Radial Recurrent Artery Flap (A Case Report) - Dr. Sokol Isaraj, Dr. Nardi Kola, (International Journal of Innovative Research in Medical Science, 2017)
The elbow defects can raise problems to plastic surgeon. Indeed, this region is characterized by thin and mobile tissues. Its reconstruction must be long-lasting, resistant to movements, to shear forces and to external support. Deep burns and other traumas of the elbow lead to soft tissue necrosis and infection, with exposure of deep structures. Adequate wound coverage of this area requires thin, pliable, and durable tissue, while optimal functional recovery requires early coverage and functional rehabilitation.1